New Elements in an Old Space? Attempts at an Extensive Approach to Roman Catholic Sacral Space – Examples from the Czech Environment at the Beginning of the 21st Century - Sklenář, Michal (Dějiny – teorie – kritika, 2022)
The article examines attempts to expand the role of sacral space through artistic interventions and other activities. It focuses on selected Roman Catholic sacral buildings in the Czech Republic at the turn of the 20th and 21st centuries. After the Second Vatican Council, and in the Czech lands more significantly after 1989, we can observe a growing trend towards creating and placing works of art in liturgical spaces, benefiting from the “genius loci” of the building or buildings. Thus, we often find works based on site-specific art concepts in abandoned chapels, churches and monasteries scarcely used for worship; their authors aim to revive or restore the sites. During the Night of the Churches, an event held across the country, sacral buildings are open to the public and parishes and Christian communities invite people to visit them for a tour, exhibition, concert, etc. The text illustrates the diversity of approaches within the ecclesial milieu through the example of Lenten veils, which, in different contexts, may serve as a declaration of “commitment to tradition” and “cultural Christianity”. The conflict of discourse does not only apply to the different approaches of individual disciplines, but it also divides the Roman Catholic environment from within because a broader consensus on “appropriate interventions”, i. e., a consensus on the external presentation of the Church, is difficult to find.